2014
DOI: 10.1002/2013jb010642
|View full text |Cite
|
Sign up to set email alerts
|

The crustal thickness of West Antarctica

Abstract: P‐to‐S receiver functions (PRFs) from the Polar Earth Observing Network (POLENET) GPS and seismic leg of POLENET spanning West Antarctica and the Transantarctic Mountains deployment of seismographic stations provide new estimates of crustal thickness across West Antarctica, including the West Antarctic Rift System (WARS), Marie Byrd Land (MBL) dome, and the Transantarctic Mountains (TAM) margin. We show that complications arising from ice sheet multiples can be effectively managed and further information conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
139
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 62 publications
22
139
1
Order By: Relevance
“…The best-fit range for the asthenospheric relaxation timescale TAUAST values is quite broad, including the prior reference value ∼ 3 kyr but extending to shorter times ∼ 1 kyr. This may be connected with low upper-mantle viscosities and thin crustal thicknesses suggested in recent work (Whitehouse et al, 2012b;Chaput et al, 2014), which will be examined in further work with full Earth models (Gomez et al, 2013(Gomez et al, , 2015Konrad et al, 2015).…”
Section: Conclusion and Further Workmentioning
confidence: 82%
See 1 more Smart Citation
“…The best-fit range for the asthenospheric relaxation timescale TAUAST values is quite broad, including the prior reference value ∼ 3 kyr but extending to shorter times ∼ 1 kyr. This may be connected with low upper-mantle viscosities and thin crustal thicknesses suggested in recent work (Whitehouse et al, 2012b;Chaput et al, 2014), which will be examined in further work with full Earth models (Gomez et al, 2013(Gomez et al, , 2015Konrad et al, 2015).…”
Section: Conclusion and Further Workmentioning
confidence: 82%
“…As in many large-scale ice-sheet models, our bedrock response is represented by a simple Earth model consisting of an elastic plate over a local e-folding relaxation towards isostatic equilibrium (elastic lithosphere relaxing asthenosphere). Based on more sophisticated global Earth models, the asthenospheric e-folding timescale is commonly set to 3 kyr (e.g., Gomez et al, 2013), but note that recent geophysical studies suggest considerably shorter timescales for some West Antarctic regions (Whitehouse et al, 2012b;Chaput et al, 2014). In further work we plan to perform large ensembles with the icesheet model coupled to a full Earth model, extending Gomez et al (2013Gomez et al ( , 2015.…”
Section: Pollard Et Al: Large Ensemble Modeling Of the Last Deglamentioning
confidence: 99%
“…Over the past two decades, several temporary seismic arrays have been deployed in Antarctica, including the TransAntarctic Mountains Seismic Experiment (TAMSEIS, 2000(TAMSEIS, -2003 (Lawrence et al, 2006), the Gamburtsev Antarctic Mountains Seismic Experiment (GAMSEIS, 2007(GAMSEIS, -2012 (Hansen et al, 2010) and the Polar Earth Observing Network/Antarctic Network (POLENET/ANET, 2007-2016) (Chaput et al, 2014). Despite their relatively sparse distribution compared to many dense seismic arrays on other continents, these three arrays combined effectively cover East and West Antarctica as well as the Transantarctic Mountains region (Fig.…”
Section: Datamentioning
confidence: 99%
“…The thickness of the lithosphere and the viscosity of the upper and lower mantle are user-defined parameters. It has been suggested that there is considerable lateral variability beneath the Antarctic continent (Morelli and Danesi, 2004;Chaput et al, 2014), from the relatively thin lithosphere and low viscosity mantle believed appropriate for the West Antarctic rift system to the thicker lithosphere and higher viscosity mantle of the craton below East Antarctica. Consequently, there have been considerable differences in the Earth model used in previous Antarctic GIA modelling studies (Peltier, 2004;Whitehouse et al, 2012b;Ivins et al, 2013).…”
Section: Glacial Isostatic Adjustment Modelmentioning
confidence: 99%